Dynamic serum albumin and outcome of peritoneal dialysis patients: A retrospective study in China - Song, Panai; Yang, Dong; Li, Jine; Zhuo, Ning; Fu, Xiao; Zhang, Lei; Zhang, Hongqing; Liu, Hong; Sun, Lin; Liu, Yinghong (Frontiers in Medicine, 2022)
Introduction: Serum albumin levels at a single time point have been shown to predict mortality in peritoneal dialysis (PD) patients. However, we believe that the dynamic change in albumin after PD may be more significant. In this study, we investigated the relationship between dynamic serum albumin and the clinical outcome of patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Methods: The participants in this study enrolled 586 patients who underwent CAPD at the peritoneal dialysis center of Second Xiangya Hospital in China. We retrospectively reviewed medical records from January 1, 2010, to December 31, 2019. Baseline serum albumin (Alb), time-averaged albumin level (TA-ALB) and serum albumin reach rate (SR: defined as the percentage of serum albumin measurements that reached ≥35 g/L) were applied as the predictor variables. All-cause mortality and cardiovascular mortality were used as the outcome variables. Hazard function of all-cause mortality and cardiovascular mortality in the study participants were examined by using Cox proportional hazard regression models. Results: Age (HR= 1.03, 95% CI 1.00-1.05), cardiovascular disease (HR= 1.80, 95% CI 1.07-3.03) and TA-ALB (HR= 0.92, 95% CI 0.85-0.99) were independent risk factors for all-cause mortality in PD patients. Patients with TA-ALB of < 33 g/L (HR= 2.33, 95% CI 1.17-4.62) exhibited a higher risk for all-cause mortality than those with TA-ALB≥36g/L. Stratified SR showed a similar trend. Patients with a <25% SR exhibited a significantly increased risk for all-cause mortality (HR =2.72, 95% CI, 1.24-5.96) by fully adjusted analysis. However, neither TA-ALB nor SR were associated with the risk of cardiovascular mortality after adjusted analysis. Conclusion: This study demonstrated that age, cardiovascular disease, and TA-ALB were independent risk factors for all-cause mortality in PD patients. TA-ALB and SR can better predict the prognosis of PD patients than baseline Alb. Dynamic changes in Alb are more clinically significant than baseline Alb in predicting mortality risk.